Pengenalan dan Cara Mengidentifikasi Makrofungi untuk Menunjang Proses Belajar Mengajar Guru dan Santriwati di Madrasah Aliyah Al-Hasanah, Bengkulu Tengah - Welly Darwis; Risky Hadi Wibowo; Helmiyetti Helmiyetti; Reza Wahyuni; Elsi Silvia; Dhea Amelia Sari; Aldi Trianda; Aulia Adriansyah (Universitas Mathla'ul Anwar Banten, 2022)
Information about the introduction and how to identify the macrofungi in the Madrasah Aliyah Al-Hasanah is still low, so it is necessary to introduce methods for dealing with macrofungi. Identification of macrofungi is one of the methods used to determine the macrofungi, whether they are pathogenic or not by looking at the morphological characteristics of the macrofungi. The activity of community service began with licensing by the Madrasah, providing material about macrofungi, the community service team shows some examples of wet herbariums for several previously identified macrofungi. After studying the macrofungi technique, the community service team and students developed skills in finding macrofungi from several wet herbariums that had been provided by the community service team, and formed study groups for participants to better understand the introduction and how to identify macrofungi. In this community service, it is hoped that the participants can develop skills in finding, discovering, identifying and preserving of the macrofungi and become apart of learning material for teachers and students. Macrofungi can also be used as medicine in the health sectors, as an environmental decomposer and useful in the economic field because they can be used as food ingredients.